Temperature-mediated fabrication, stress-induced crystallization and transformation: atomistic simulations of additively manufactured amorphous Cu pillars. (22nd August 2019) - Zhao, Ziyu; Liu, Jinxing; Soh, Ai Kah; Tang, Chun
Abstract: Additive manufacturing (AM) is an emerging and promising technology. In this manuscript, an attempt is made to simulate an AM process via molecular dynamics simulations. Amorphous Cu pillars are built by bundling melting Cu wires parallelly one by one, with a particular temperature-controlling procedure through the use of 'mediate temperature'. Thus, the volume fraction of the amorphous phase becomes adjustable. Uniaxial tests are conducted on the pillars after free relaxation. The mediate temperature is found to play a profound role in atomic arrangement, which governs the volume fractions of amorphous and crystalline phases. The results obtained also show that crystallization prevails when the pillar is subjected to an external tension. Furthermore, such a stress-induced crystallization serves as the dominant plastic mechanism instead of dislocation, and a vibrating uniaxial loading is found to accelerate the transformation from an amorphous to a crystalline phase, compared with a monotonic tension.